A New Framework for Understanding Memories and Preference for Music. (25th August 2020) - Lamont, Alexandra; Loveday, Catherine
What can musical memories tell us about preference, and what can musical preferences tell us about memory? In this article we contrast the two perspectives using a dialogic conversation, drawing on insights brought into relief at the recent Music and Lifetime Memories conference. We use dialogue to present two different bodies of relevant background literature and theory and consider their overlaps, interactions, and contradictions in depth. We then compare our two different approaches to the same dataset – the Desert Island Discs archive – which provide complementary perspectives and insights. We interpret each other's analyses from our own perspectives, and finally conclude with reflections on future directions for the field.